2017
DOI: 10.33225/jbse/17.16.459
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Pre-Service Science Teachers’ Conceptual Understanding About Boiling by Dialogic Teaching

Abstract: In order to reach students who can efficiently use intended scientific understandings, it is important to have science teachers without conceptual difficulties. The aim of present research is to enhance pre-service science teachers’ conceptual understanding about boiling by dialogic teaching. The sample consisted of forty-three pre-service science teachers in their first year of teacher education. Dialog-based instructional activities were conducted in a chemistry laboratory course. Audio recordings of classro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Vaporization starts when the partial pressure of water in the air is less than the saturated vapor pressure of the environment. The boiling point of a liquid is reached at a specific temperature when the vapor pressure of the liquid is equal to the vapor pressure of the atmosphere [59], [60] 3. In the equilibrium system with a constant volume, the temperature change has no impact on the quantity of liquid or vapor Liquid-vapor equilibrium in a closed container tends to reestablish at a certain point, and the amount of vapor varies according to volume or temperature [16], [29] 4.…”
Section: Vaporization Starts With Boiling or Else Liquid Boils Becaus...mentioning
confidence: 99%
See 3 more Smart Citations
“…Vaporization starts when the partial pressure of water in the air is less than the saturated vapor pressure of the environment. The boiling point of a liquid is reached at a specific temperature when the vapor pressure of the liquid is equal to the vapor pressure of the atmosphere [59], [60] 3. In the equilibrium system with a constant volume, the temperature change has no impact on the quantity of liquid or vapor Liquid-vapor equilibrium in a closed container tends to reestablish at a certain point, and the amount of vapor varies according to volume or temperature [16], [29] 4.…”
Section: Vaporization Starts With Boiling or Else Liquid Boils Becaus...mentioning
confidence: 99%
“…When the system reaches equilibrium, the liquid water and vapor phases will evaporate and condense at the equal rate [16] 5. The water's state transition depends only on the temperature Pressure in the system also affects the phase transition of water [16], [60] 6.…”
Section: Vaporization Starts With Boiling or Else Liquid Boils Becaus...mentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, it was observed that the mathematical discourse of the teachers was more effective in the development of the extremal discourse types in the mathematical discourse core. Similarly, Demirbağ (2017) emphasized that different types of discourse contributed to the development of arguments by pre-service teachers and the role of the teacher was significant in every stage between the discussion of ideas and the conclusion. Thus, it could be suggested that the teacher's mathematical discourse determine the participation of the students in the class to express their views.…”
Section: Figurementioning
confidence: 99%